Cross-sectional study on prevalence and consequences of screen time on physical and mental health in children in the era of COVID-19 - Neha Thakur (Rai); Arvind Kumar Singh; Narendra Rai; Devesh Kumar Shukla (Asian Journal of Medical Sciences, 2022)
Background: With the ongoing growth and expansion of digital media and COVID-19 pandemic, children are inclining more and more toward spending time on digital media as compared to outdoor sports, leading to poor physical and mental growth. Developed nations have already set up a screen time guideline which is yet to be established in developing nations. This study was conducted with the objectives of identifying the needs of screen time guidelines and to study the impact of screen time on mental and physical health in children.